Condiciones de movimiento geostrofico para la corriente costera de Costa Rica (ING) - Brenes, Carlos L. (1985)
The geostrophic current and the volumen transport have been calculated, for the month of January 1969, for a section off Golfo Dulce, using the Montgomery´s method. During this period the Costa Rica Coastal Current was flowing northwestward, along the continental shelf, with a velocity up to 20cm/s, related to 67 cl/ton isanosteric surface. Under this current, a sub-surface flow in the opposite directions was found with an associated maximum velocity of 11 cm/s. The volume transport generated by these currents has been estimated  in about 1.26 Sv for the northwest current and 1.24 Sv for the southeast flow. In the first case, the total transport occurred at the surface layer, above the 250 cl/ ton isanoteric surface; in the second case, the transport shows up at in the layer between the 160 cl/ton and 200 cl/ton.At the southern end of the section, southeast and northwestward flows have been detected with velocities and transports of 33 cm/s, 0.55 Sv , and 39 cm/s, 3.54 Sv  respectively.